Asymptotic Abelian Complexities of Certain Morphic Binary Words - Markus A. Whiteland (Institut für Informatik, Justus-Liebig-Universität Giessen, 2022)
We study asymptotic Abelian complexities of morphic binary words. We complete
the classification of upper Abelian complexities of pure morphic binary words initiated
recently by F. Blanchet-Sadri, N. Rampersad, and N. Fox. We also study a class of
morphic binary words having different asymptotic factor complexities despite having
the same asymptotic Abelian complexity.